Strong Convergence of Two Iterative Algorithms for Nonexpansive Mappings in Hilbert Spaces. (12th October 2009) - Yao, Yonghong; Liou, Yeong Cheng; Marino, Giuseppe
Abstract : We introduce two iterative algorithms for nonexpansive mappings in Hilbert spaces. We prove that the proposed algorithms strongly converge to a fixed point of a nonexpansive mappingT .